Manual of Operations for the Schools-on-the-Air on Smart Rice Agriculture - Philippine Department of Agriculture (2020)
This manual serves as a guide for all partners involved in the School-on-the- Air on Modern Rice Agriculture program. It has six chapters: (1) Context, (2) Introduction, (3) Implementation scheme, (4) Organizing and conducting the SOA, (5) Logistical requirements, and (6) Reporting procedures. Also included are the various activities from the pre-broadcast to the post-broadcast phase, roles and responsibilities of partners involved in the program, references on modern, climate-smart rice agriculture and a sample SOA curriculum.